Library School Education for Medical Librarianship - Roper, Fred W. (1979)
This paper reviews the current situation in library school education for medical librarianship in the United States and Canada based on information from a questionnaire sent to teachers of courses in medical librarianship in accredited library schools. Since 1939, when the first course devoted entirely to medical librarianship was offered at Columbia University, courses have been introduced into the curricula of at least forty-seven of the ALA-accredited library schools. In 1978 there were seventy courses available through forty-seven library schools. Possibilities for specialization in medical librarianship are examined. Course content is reviewed. Implications of the MLA certification examination for library school courses are explored.